2020
DOI: 10.3390/vaccines8040705
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude and Determinants of Missed Opportunities for Childhood Vaccination in South Africa

Abstract: Missed opportunities for vaccination (MOV) may be among the factors responsible for suboptimal vaccination coverage in South Africa. However, the magnitude and determinants of MOV in the country are not known. Thus, this study seeks to assess the prevalence and determinants of MOV in the country. South Africa is sub-divided into nine administrative provinces. We used nationally representative data from the 2016 South African Demographic and Health Survey. We considered MOV to have occurred if a child aged 12–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
0
11
3
Order By: Relevance
“…Changes to the anti-HBc IgM testing practices, particularly in Mpumalanga and Eastern Cape provinces, may have contributed to the change in rates over time. Given these findings and provincial disparities within South Africa, further investigations to better understand risk behaviour, testing practices and vaccination coverage, are warranted in Limpopo, Mpumalanga, Eastern Cape and Kwazulu-Natal provinces [58]. Where applicable, targeted provincial interventions would subsequently decrease countrywide incidence of HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Changes to the anti-HBc IgM testing practices, particularly in Mpumalanga and Eastern Cape provinces, may have contributed to the change in rates over time. Given these findings and provincial disparities within South Africa, further investigations to better understand risk behaviour, testing practices and vaccination coverage, are warranted in Limpopo, Mpumalanga, Eastern Cape and Kwazulu-Natal provinces [58]. Where applicable, targeted provincial interventions would subsequently decrease countrywide incidence of HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Others have analyzed proportion of children who experience MOVs across a cross-section of archived DHS datasets [ 58 , 59 ], but we believe this is the first longitudinal analysis showing both visit-based and child-based indicators. VCQI, and its underlying algorithm, addresses the need that other researchers have recently noted in this journal for vaccine-specific and dose-specific indicators [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings from our preliminary analysis of the 2016 South African Demographic and Health Survey data suggest that MOV constitutes a major burden, with a national prevalence of 42% and a Western Cape provincial prevalence of 36% [ 28 ]. The study identified individual-level factors, such as maternal attendance of antenatal care during pregnancy, and geographical factors, such as province of residence, as significant determinants of MOV.…”
Section: Missed Opportunities For Vaccination As a Driver Of Suboptimal Immunisation Coveragementioning
confidence: 99%